TI_GERICHTE 60.2010.314 vom 10. Dezember 2010 , Istanza di indennità per ingiusto procedimento. Torto morale. Danno materiale - TI Tribunale d'appello (2010)
Istanza di indennità per ingiusto procedimento. Torto morale. Danno materiale